The Guarango in the Guano Canton of the Province of Chimborazo - Ecuador - Stalin Efrén, Arguello Erazo (2017)
In recent years there has been a growing production of Guarango native product of the area, but there is no means to carry out the marketing of products and by-products that can be derived from this product. To the world market and exploit all the benefits that this could have.